Synergistic silencing of α-globin and induction of γ-globin by histone deacetylase inhibitor, vorinostat as a potential therapy for β-thalassaemia - Mettananda, S; Yasara, N; Fisher, C; Taylor, S; Gibbons, R; Higgs, D (Nature Research, 2019)
β-Thalassaemia is one of the most common monogenic diseases with no effective cure in the majority of patients. Unbalanced production of α-globin in the presence of defective synthesis of β-globin is the primary mechanism for anaemia in β-thalassaemia. Clinical genetic data accumulated over three decades have clearly demonstrated that direct suppression of α-globin and induction of γ-globin are effective in reducing the globin chain imbalance in erythroid cells hence improving the clinical outcome of patients with β-thalassaemia. Here, we show that the histone deacetylase inhibitor drug, vorinostat, in addition to its beneficial effects for patients with β-thalassaemia through induction of γ-globin, has the potential to simultaneously suppress α-globin. We further show that vorinostat exhibits these synergistic beneficial effects in globin gene expression at nanomolar concentrations without perturbing erythroid expansion, viability, differentiation or the transcriptome. This new evidence will be helpful for the interpretation of existing clinical trials and future clinical studies that are directed towards finding a cure for β-thalassaemia using vorinostat.